Exploring the Anthropometric Attributes of Cosmetologists in Yenagoa, Nigeria - Okoro, Chukwudi Emmanuel; Adewale, Ibrahim Olufemi; Okonkwo, Samuel Chinedu; Nwosu, Ijeoma Ifeoma (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Cosmetologists are generally defined as individuals who work in retail- or home-based salons and provide a wide range of beauty services, including hair shampooing and styling, manicures, pedicures, and scalp and facial treatments. Hairdressing and cosmetology are common occupations, and several million individuals are employed as hairdressers and cosmetologists (HC) worldwide. Hairdressers can be exposed to a variety of chemicals on a daily basis, due to their use of hair products, shampoos, permanent wave solutions, hair dyes, and hair sprays. Reproductive toxic effects have been reported for some of these agents. The study was conducted in Yenagoa Local Government Area (YELGA), Bayelsa State. The State is a cosmopolitan state in the southern part of Nigeria, which is geopolitically located within Latitude 415 North, 523 South, Latitude 522 West and 645 East. It has an area of 706km. Ethical approval was sought from the Ethical Committe ll of Niger Delta University, Wilberforce Island, Bayelsa state, Nigeria. It was carried out with compliance with the principle of Helsinki declaration of 1975 as revised in 2008. Informed consent was obtained from all the recruited volunteers who were made to know the reasons their blood and urine samples were needed for the research. A total number of twenty five (25) Urine and Blood samples were randomly selected from cosmetologist in yenagoa.The most common chemicals mentioned in this study are nitrosamines in hair dye, toluene in nail polish, and formaldehyde in both hair dye and nail polish. This study shows that the health status of cosmetologists residing in yenagoa local government area are not affected by the chemicals they are exposed to, due to the fact that the parameters worked on are unable to pick out certain abnormalities that may determine the overall health status of these subjects. The abnormalities observed from this study may arise from an individual’s overall health status, genetic predisposition, lifestyle and personal hygiene.